(untitled) (Journal of history, 2021)
The article is devoted to the study of the color concept problem in the ethnic history of nomads. The purpose of this article is to study the issue of color designation semantics in the ethnic structure of the Turks in the historical, etymological, ethnocultural aspects. The significance of the problem is due to the unresolved interpretation of the connotation of color, its genesis in the names of ethnonyms, the need to systematize existing knowledge, as well as an integrated approach to the study of subjects related to the formation of the cultural identity that belong to nomadic world population. The topic assumes the solution of such problems as defining the problematics in the context of the study of color-denoting vocabulary in the cultural tradition, identifying a semiotic approach in the analysis of the color con- cept, substantiating the prospects for the potential of color attribution in the study of the ethnic history problems of nomads. The theoretical premise of studying the issue was the idea that the specificity of coloristic perception is included in the worldview system, it is present in the form of symbols and signs that convey and reveal the semiotic sphere of ethnocultural consciousness. The study traces the tradition of the historical analysis of the color designation of tribes and clans based on classical scientific works in the field of Turkic history, folklore and linguistics. The source base was written records, toponymy data and oral historiology. The main research methods were: comparative historical, semiotic, semantic analysis. The specificity of coloristic perception is included in the worldview system, it is present in the form of symbols and signs that convey and reveal the semiotic sphere of ethnocultural consciousness. As a result of the study, a conclusion was made about the ancient origins of the phenomenon of color, the existence of archetypes of color images dating back to the mythology of the Turks. Color attribution in the ethnonymy of nomads has a wide range of designations: from direct to symbolic. The color designa- tion semantics depends on the historical context of application, the specifics of the culture of its use by the people, the historical conditions for the formation of the tribal composition. Key words: color designation, symbolism, ethnonym, culture, white, black, yellow, variegated.